Compound enzyme nanogel as well as preparation method and application thereof
The preparation of composite enzyme nanogels through polymerization in vivo has solved the problems of poor stability of protein preparations and low drug loading rate, achieved efficient delivery and long-acting biological activity, and improved the efficiency of enzyme cascade reaction.
Patent Information
- Application Number
- CN202411614492.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
Existing protein preparations have problems such as poor stability, low drug loading rate and early leakage, making it difficult to deliver effectively and maintain biological activity in the body.
Compound enzyme nanogels are prepared through in-situ polymerization reaction, and the double bond functional modification of protease is achieved by electrostatic adsorption of monomeric polymer materials, and protein in situ polymerization and self-assembly cross-linking is used to in-situ polymerization of proteins and to form nanosized by crosslinking agents and binders. gel.
It significantly improves the load and stability of protein drugs, reduces the spatial distance between different enzymes, improves the efficiency of enzyme cascade reaction, extends the half-life, and maintains biological activity.
Smart Images

Figure CN119454920A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a composite enzyme nanogel and a preparation method and application thereof. Background Art
[0002] Proteins play an important role in many physiological and pathological processes, including metabolism, cell communication, cell growth and development, etc. Compared with traditional small molecule drugs, protein therapy has higher specificity, better activity and better biocompatibility. Currently, protein-based therapies have had a significant impact on the treatment of many important human diseases, including cancer, diabetes, inflammatory diseases and infections. However, due to the complexity and high specificity of protein structure, most of them have problems such as poor stability, easy degradation, poor transmembrane ability and immunogenicity. Most of the proteins currently sold on the market exhibit extracellular activity, but due to the complex environment in the body, their actual bioavailability is relatively low. Therefore, it is crucial to develop safe, stable and efficient protein preparations.
[0003] In order to improve the stability of proteins, biocompatible polymers have been widely used to improve protein preparations. For example, polyethylene glycol (PEG) modification is an effective method to extend the half-life of protein drugs and reduce protein degradation in the blood circulation. At present, a number of PEGylated protein drugs have been approved by the FDA for marketing, such as PEGylated L-asparaginase for the treatment of acute lymphoblastic leukemia and PEGylated arginine deiminase for anti-tumor treatment. However, since this method requires chemical modification of proteins, this may lead to changes in the amino acid structure of the active site or near the active site in the protein, which may lead to partial loss of protein biological activity. In recent years, with the rapid development of nanotechnology, nanocarriers, such as liposomes, polymer micelles, metal organic frameworks and inorganic nanoparticles, have become the preferred solution for delivering protein drugs. However, most of these carriers load proteins by adsorption and encapsulation, which have problems such as low drug loading rate and poor stability. Summary of the invention
[0004] Aiming at the defects of poor stability, low drug loading rate, early leakage and the like of protein preparations in the prior art, the present invention prepares a composite enzyme nanogel through in-situ polymerization reaction.
[0005] The composite enzyme nanogel comprises the following components in parts by weight: 12 to 1250 parts of composite protease; 5 to 210 parts of monomer polymer material; 12 to 120 parts of binder; and 12 to 120 parts of cross-linking agent.
[0006] The composite protease is any two or more of glucose oxidase (GOD), catalase (CAT), superoxide dismutase (SOD), horseradish peroxidase (HRP), glutathione peroxidase (GPx), lactate oxidase (LOD), heme oxygenase (HbOx) and quinone oxidoreductase (QOR);
[0007] The present invention uses glucose oxidase and catalase as protein drug models and expands them to the delivery of multiple proteins, such as superoxide dismutase, horseradish peroxidase, glutathione peroxidase, lactate oxidase, heme oxygenase and quinone oxidoreductase, so that it can treat diseases such as diabetes, cancer, inflammatory diseases and infections more safely and effectively.
[0008] The monomer polymer material is any one or more of 2-methylallylamine (MAPA), N,N-dimethylacrylamide (DMAA), 2-(diethylamino)ethyl methacrylate (DEAEMA), propyl methacrylate, 2-(dimethylamino)ethyl methacrylate (DMEAEMA), 3-methylbut-3-en-1-amine (MBBA), allylamine (AA), allyltrimethylammonium chloride (ATMAC) and diallyldimethylammonium chloride (DADMAC).
[0009] Nanogel is a swollen cross-linked gel with nanometer size and high water-carrying capacity. Its water-containing cavity has environmental benefits for protein encapsulation and delivery, and the cross-linked network can limit the free movement of the encapsulated protein to a certain extent, thereby reducing aggregation and increasing stability. The present invention greatly increases the protein drug loading capacity by performing polymerization reaction in situ on the protein; it can load multiple protein enzymes at the same time, effectively reducing the steric hindrance of the protein, and greatly improving its cascade reaction efficiency while improving its stability.
[0010] Furthermore, in the composite protease:
[0011] 1) The mass ratio of glucose oxidase to catalase is 0.5:(0.1-15); or
[0012] 2) The mass ratio of superoxide dismutase to catalase is 0.1:(0.5-30); or
[0013] 3) The mass ratio of horseradish peroxidase to catalase is 0.2:(1-10); or
[0014] 4) The mass ratio of lactate oxidase to catalase is 0.1:(0.2-12); or
[0015] 5) The mass ratio of any one of glucose oxidase, superoxide dismutase, horseradish peroxidase, glutathione peroxidase, lactate oxidase and catalase is (1-10): (0.5-15); or
[0016] 6) The mass ratio of any one of glucose oxidase, superoxide dismutase, horseradish peroxidase, glutathione peroxidase, lactate oxidase, catalase and heme oxygenase is (2-30): (5-15): (3-20); or
[0017] 7) The mass ratio of glucose oxidase, superoxide dismutase, horseradish peroxidase, glutathione peroxidase and lactate oxidase, catalase and quinone oxidoreductase is (1-15): (2-25): (1-30); the nanogels formed by the composite proteases in different ratios have different properties, such as the particle size of the nanogels.
[0018] Furthermore, the binder is at least one of acrylamide, acrylic acid, 2-hydroxyethyl acrylate, N-isopropyl acrylamide, glyceryl methacrylate (GM), methacryloyl hydrazide and 3-allyloxy-1,2-propylene glycol.
[0019] Furthermore, the crosslinking agent is at least one of allyl methacrylate (AMA), N,N'-methylenebisacrylamide, poly(ethylene glycol) diacrylate, multi-arm poly(ethylene glycol) diacrylate, N,N'bis(acryloyl)cystamine, N,N'-(1,2-dihydroxyethylene)diacrylamide, N,N-diallylacetamide, N-methyldiallylamine, triallylamine, 1,3-bis(propyleneoxy)-2-propanol, N,N'-diallyltartaric acid diamide, 1,3-diallyl-2-thiourea and ethylene glycol dimethacrylate (EGD).
[0020] Furthermore, the particle size of the complex enzyme nanogel is 10 to 1000 nm, preferably 50 to 200 nm.
[0021] Furthermore, the mass ratio of the composite protease to the monomer polymer material is (1-140):60;
[0022] The present invention also provides a method for preparing the composite enzyme nanogel, comprising the following steps:
[0023] The composite protease is weighed by weight and placed in a solvent, a monomer polymer material is added, and the mixture is reacted by electrostatic adsorption for 2 to 12 hours under stirring at room temperature to obtain a mixture; the mixture is nitrogen blown for 1 to 3 hours, a cross-linking agent and a binder are added, and the mixture is stirred and reacted for 3 to 10 hours to obtain the composite enzyme nanogel.
[0024] Furthermore, the mass ratio of the solvent to the cross-linking agent is 10:(8.5-13).
[0025] Furthermore, the mass volume ratio of the composite protease to the solvent is 1:(5-20).
[0026] Furthermore, the preparation step also includes: filtering and sterilizing the prepared complex enzyme nanogel.
[0027] During the preparation process of the composite enzyme nanogel of the present invention, the electrostatic adsorption effect of the monomer polymer material is utilized to realize the double bond functionalization modification of the protease, and under the action of the cross-linking agent and the binder, the double bond free radicals initiate the in-situ polymerization self-assembly cross-linking of the protein to form the nanogel; in the structure of the above-mentioned cross-linked network, the nanogel reduces the spatial distance between different enzymes while increasing the enzyme loading capacity and enzyme stability, thereby effectively improving the efficiency of the cascade reaction between enzymes.
[0028] Furthermore, the electrostatic adsorption reaction time is preferably 5 to 10 hours.
[0029] Furthermore, the preparation time of the complex enzyme nanogel is 4.5 to 12 hours.
[0030] The present invention also provides the use of the composite enzyme nanogel in preparing medicines for treating cancer, inflammatory diseases, diabetes and infections.
[0031] In summary, compared with the prior art, the present invention achieves the following technical effects:
[0032] 1. The composite enzyme nanogel of the present invention has good gelling property.
[0033] The protein loading capacity is increased, the protein enzyme loading capacity is higher than 49%, up to 85%, and it has strong stability and good safety. In addition, the stability of the nanogel structure gives the protease a higher half-life, and does not affect the biological activity of the protease itself, and can continuously and effectively carry out the enzyme cascade effect, greatly reducing the dosage concentration and the number of doses, and improving patient compliance.
[0034] 2. The raw materials of the composite enzyme nanogel of the present invention are cheap, the preparation process is relatively simple, the preparation cost is low, it is convenient for industrial production, conducive to large-scale promotion and application, and promotes technological innovation.
[0035] 3. The complex enzyme and monomer polymer materials in the present invention are both low-toxic, safe and biodegradable. When applied to daily chemicals, they have stable physical and chemical properties and can give daily chemicals the multiple functions of continuously consuming glucose, scavenging hydrogen peroxide free radicals and generating oxygen. Compared with traditional products, the effect is more significant, lasts longer and is more stable.
[0036] 4. The composite enzyme nanogel of the present invention has a certain positive effect on reducing blood sugar in diabetic wounds and inflammatory diseases (such as diabetes, dry eyes, cancer and infection, etc.). BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 The schematic diagram of the nanogel enzyme cascade reaction of Example 5 of the present invention (left figure) and the microstructure diagram of the composite enzyme nanogel of Example 1 (right figure);
[0039] Figure 2 It is the enzyme cascade effect diagram of Example 5 of the present invention and Comparative Example 1;
[0040] Figure 3 The dynamic particle size distribution result of Example 5 of the present invention;
[0041] Figure 4 The particle size distribution diagrams of Example 5, Examples 13 to 36, and Comparative Examples 1 to 2 of the present invention;
[0042] Figure 5 The fluorescence resonance energy transfer verification results of Example 5 and Comparative Example 1 of the present invention are shown;
[0043] Figure 6 The oxygen generation analysis diagram of Example 5 of the present invention and Comparative Examples 1 and 2; wherein DO represents "dissolved oxygen" in mg / mL;
[0044] Figure 7 The free radical scavenging effect diagram of Example 5 of the present invention and Comparative Example 2 is shown. DETAILED DESCRIPTION
[0045] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work should fall within the scope of protection of the present invention.
[0046] Source of raw materials:
[0047] Glucose oxidase: Shanghai Aladdin Biochemical Technology Co., Ltd., G401535;
[0048] Superoxide dismutase: Shanghai Aladdin Biochemical Technology Co., Ltd., S128537
[0049] Catalase: Shanghai Aladdin Biochemical Technology Co., Ltd., C163049;
[0050] Horseradish peroxidase: Shanghai Aladdin Biochemical Technology Co., Ltd., P105528;
[0051] Lactate oxidase: Shanghai MacLean Biochemical Technology Co., Ltd., L914182;
[0052] Propyl methacrylate: Shanghai MacLean Biochemical Technology Co., Ltd., D948661;
[0053] 2-(Dimethylamino)ethyl methacrylate: Shanghai MacLean Biochemical Technology Co., Ltd., E808723;
[0054] Allyl methacrylate: Shanghai MacLean Biochemical Technology Co., Ltd., A800501;
[0055] N, N'-methylenebisacryloyl: Shanghai MacLean Biochemical Technology Co., Ltd., N828383;
[0056] Acrylamide: Shanghai MacLean Biochemical Technology Co., Ltd., A800656.
[0057] The preparation methods of the composite enzyme nanogels of the embodiments and comparative examples are as follows:
[0058] (1) The protease is placed in deionized water at a mass-to-volume ratio of 1:10, and then vortexed to disperse it evenly, and then a monomer polymer material is added. The mixture is reacted by electrostatic adsorption for 5 to 10 hours under stirring at room temperature to obtain a double-bond functionalized protease.
[0059] (2) The proteases obtained in (1) are mixed into the same container, vortexed to mix evenly, and then a binder is added. After nitrogen blowing for 1 hour, a cross-linking agent is added. The free radical-initiated polymerization reaction time is 4.5 to 12 hours to obtain a composite enzyme nanogel with a stable structure.
[0060] (3) Sterilize the prepared composite enzyme nanogel by filtration sterilization: Assemble the suction filtration device and pre-pad the filter membrane. Check the seal of the suction filtration bottle before sterilization and plug it with gauze or cotton. When using, ensure that the collection bottle is sterile. After suction filtration, pour the filtered solution into a sterilized empty reagent bottle under sterile conditions.
[0061] The composition ratios of the composite enzyme nanogels prepared in Examples 1 to 12 are shown in Table 1, with the unit being mg.
[0062] Table 1
[0063]
[0064] The test solutions of Examples 1 to 12 were characterized, and the enzyme loading and enzyme activity under high temperature conditions were evaluated.
[0065] (1) Characterize the nanogel particles prepared in Example 1.
[0066] The test sample was dispersed in deionized water to a concentration of 1 mg / mL, and the sample solution was stirred thoroughly to make it dispersed evenly. Then, the microstructure of the nanogel was characterized by scanning electron microscopy. Figure 1 As shown in the figure on the right, the microstructure of the complex enzyme nanogel is spherical, and its particle size is consistent with the results of dynamic particle size measurement.
[0067] (2) Enzyme loading
[0068] Detection method: Sample determination: send the sample to the high performance liquid chromatography detector for detection, collect data, and obtain the enzyme concentration through standard curve regression calculation.
[0069] Liquid chromatography conditions: C18 chromatographic column, mobile phase a was an aqueous solution containing 0.1% formic acid, mobile phase b was acetonitrile, column temperature was 40°C, flow rate was 0.8 ml / min, gradient elution, the initial mobile phase ratio was mobile phase a: mobile phase b at 95:5 and maintained for 0.5 min, within 0.5 min, mobile phase b was increased to 70% and maintained under this condition for 2.0 min, then within 0.5 min, mobile phase b was reduced to 5% and maintained for 0.5 min, and the total acquisition time was 4 min.
[0070] (3) Enzyme cascade effect
[0071] A certain amount of Example 5, glucose and Comparative Example 1 samples were added to different groups, and the change in the concentration of glucose in the system was measured.
[0072] The results are as follows Figure 2 As shown, Example 5 and Comparative Example 1 can continuously consume glucose, while the concentration of the glucose group alone remains unchanged. Therefore, the effect and trend of glucose consumption in Example 5 are basically consistent with those in Comparative Example 1, indicating that the composite enzyme nanogel of the present invention does not affect the activity function of glucose oxidase and has an enzyme cascade effect. Figure 1As shown in the left figure, the composite enzyme nanogel with uniform particle size can oxidize high-concentration glucose into gluconic acid and hydrogen peroxide in the presence of oxygen. The reaction product hydrogen peroxide is further catalyzed to produce water and oxygen under the action of catalase. The oxygen product continues to participate in the glucose oxidation reaction, thereby producing a cascade effect.
[0073] (4) Enzyme cascade reaction activity (%)
[0074] The oxygen consumption was compared with that of natural GOD and CAT under pH=7, 50℃ water bath conditions within 30 minutes.
[0075] Oxygen consumption detection method: In sulfuric acid acid medium, potassium dichromate is used as oxidant, silver sulfate is used as catalyst, mercuric sulfate is used as masking agent for chloride ions, sulfuric acid acidity of digestion reaction solution is 9 mol / L, heating is used to make the digestion reaction solution boil, and the boiling point temperature of 148℃±2℃ is the digestion temperature. Cool with water and heat under reflux for 2h. After the digestion solution cools naturally, ferrochlore is used as indicator and ammonium ferrous sulfate solution is used to titrate the remaining potassium dichromate. The oxygen consumption value of the sample is calculated based on the consumption of ammonium ferrous sulfate solution.
[0076] The evaluation results of enzyme loading and enzyme cascade reaction activity of Examples 1 to 12 are shown in Table 2:
[0077] Table 2
[0078]
[0079] As shown in Table 2, the enzyme loading of the nanogels prepared in the examples is above 49%, among which the enzyme loading of Example 5 is higher, 85%, and the enzyme activity is the best, and the performance is characterized by this formula. The enzyme activities of Examples 6 to 12 are equivalent to those of Example 5, with no significant difference, but there are certain differences in the enzyme loading. Comprehensive analysis shows that under the same conditions, the nanogel formed in Example 5 has a higher enzyme loading capacity while ensuring the activity of the enzyme cascade reaction.
[0080] Based on Example 5, the particle size distribution and stability of the composite enzyme nanogel were further investigated.
[0081] The composition ratios of the composite enzyme nanogels prepared in Examples 13 to 36 are shown in Tables 3 and 4, with the unit being mg.
[0082] Table 3
[0083]
[0084] Table 4
[0085]
[0086]
[0087] The test solutions of Example 5 and Examples 13 to 36 were evaluated for particle size and particle size stability at room temperature.
[0088] The particle size test method is:
[0089] Take 1 mL of the test solution, dilute it with an appropriate amount of purified water, add the dilution into a cuvette, use a 380ZLS particle size and Zeta potential detection analyzer to measure, and record data such as the average particle size.
[0090] The evaluation results are shown in Table 5 and Figure 4 As shown, Figure 4 The dynamic particle size distribution result of Example 5 shows that the particle size range of Example 5 is 100 to 300 nm.
[0091] Table 5
[0092]
[0093]
[0094] As shown in Table 5, the particle size distribution of Examples 13 to 36 is basically consistent with that of Example 5, and good stability is maintained within 60 days at room temperature. Therefore, the composite enzyme nanogel technology has good stability while having a high enzyme loading capacity, and can realize the co-loading of two or more enzymes, thereby achieving an efficient enzyme cascade effect.
[0095] Comparative Example 1
[0096] Compared with Example 5, the nanogel was prepared with 10 mg of glucose oxidase as a single component.
[0097] Comparative Example 2
[0098] Compared with Example 5, the nanogel was prepared with 300 mg of catalase as a single component.
[0099] Comparative Example 3
[0100] Compared with Example 5, the nanogel was prepared using papain and lactate dehydrogenase as composite enzyme components.
[0101] Comparative Example 4
[0102] Compared with Example 5, the nanogel is prepared using caprolactam as the monomer polymer material.
[0103] Comparative Example 5
[0104] Compared with Example 5, the weight portions of glucose oxidase and catalase were 5 parts to prepare the nanogel.
[0105] Comparative Example 6
[0106] Compared with Example 5, the weight portions of glucose oxidase are 50 parts and catalase are 1500 parts to prepare nanogel.
[0107] Comparative Example 7
[0108] Compared with Example 5, the weight portion of the monomer polymer material is 3 parts to prepare the nanogel.
[0109] Comparative Example 8
[0110] Compared with Example 5, the weight portion of the monomer polymer material is 280 parts of the prepared nanogel. Example 5 and Comparative Examples 1 and 2 were selected to perform the following performance characterization:
[0111] 1. Fluorescence resonance energy transfer of complex enzyme nanogel
[0112] Test method: The test sample was dispersed in deionized water to a concentration of 1 mg / mL, and the solution was stirred thoroughly to make it dispersed evenly; then the construction of the nanogel was characterized by the fluorescence absorption method.
[0113] The results are as follows Figure 5 As shown, obvious energy transfer occurred in the fluorescence absorption of the composite enzyme nanogel, indicating that the composite enzyme nanogel was successfully constructed.
[0114] 2. Situation of oxygen production
[0115] Experimental method: With water as a blank control, the B10 portable oxygen gas detector was used to detect and analyze the oxygen generated in the aqueous solution of the comparative example and the example samples. DO stands for "dissolved oxygen", which refers to the content of oxygen dissolved in water, usually expressed as the oxygen concentration per unit volume of water, in mg / L.
[0116] The results are as follows Figure 6 As shown, the oxygen generated by the composite enzyme nanogel is significantly different from that of Comparative Examples 1 and 2, and the amount of oxygen generated by the composite enzyme nanogel is significantly improved.
[0117] 3. Evaluation of the scavenging effect of hydrogen peroxide free radicals
[0118] Different groups were added with a certain amount of samples of Example 5 and Comparative Example 2, and the OD in the system was measured. 240 The changes in scavenging activity of hydrogen peroxide free radicals were evaluated.
[0119] The results are as follows Figure 7 As shown, the effect and trend of scavenging hydrogen peroxide free radicals in Example 5 are basically consistent with those in Comparative Example 2, which means that the catalase in the composite enzyme nanogel can independently play its function and role.
[0120] 4. Enzyme cascade effect
[0121] A certain amount of Example 5, glucose and Comparative Example 1 samples were added to different groups, and the concentration change of glucose in the system was measured. The results showed that Example 5 and Comparative Example 1 could continuously consume glucose, while the concentration of the glucose group alone remained unchanged. Therefore, the effect and trend of glucose consumption in Example 5 were basically consistent with those in Comparative Example 1, indicating that the composite enzyme nanogel of the present invention did not affect the activity function of glucose oxidase and had an enzyme cascade effect.
[0122] Example 5 and Comparative Examples 3 to 8 were selected to characterize the following nanogel properties:
[0123] 1. Particle size of Example 5, Comparative Example 3, Comparative Example 5 and Comparative Example 6
[0124] Table 6
[0125] Example 5 Comparative Example 3 Comparative Example 5 Comparative Example 6 Particle size (nm) 195 246 84 359
[0126] The results showed that compared with Example 5, the particle size of the nanogel prepared by using other proteases (Comparative Example 3) was too large; when the amount of the composite enzyme was less or more, the particle size of the prepared nanogel was too small or too large, thus affecting the gelling performance.
[0127] 2. Gel Formation of Example 5, Comparative Examples 4, 7 and 8
[0128] By observing the gelation of protease gel, it was found that when caprolactam was used as the monomer polymer material in Comparative Example 4, it was unable to polymerize GOD and CAT to form a polymerized protease; and when the amount of monomer polymer material in Example 5 was too much or too little, its gelation ability was weak or too hard, thereby affecting the subsequent preparation of nanogel.
[0129] In summary, the present invention discloses a composite enzyme nanogel. In the preparation process of the composite enzyme nanogel of the present invention, the electrostatic adsorption of monomer polymer materials is used to realize the double bond functionalization modification of the protease, and under the action of the cross-linking agent and the binder, the double bond free radicals are used to initiate the in-situ polymerization self-assembly cross-linking of the protein to form a nanogel; in the structure of the cross-linked network, the nano-sized nanogel increases the enzyme loading and enzyme stability while reducing the spatial distance between different enzymes, effectively improving the efficiency of the cascade reaction between enzymes.
[0130] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite enzyme nanogel, characterized in that: In parts by weight, it includes the following components: The composite protease is any two or more of glucose oxidase, catalase, superoxide dismutase, horseradish peroxidase, glutathione peroxidase, lactate oxidase, heme oxygenase and quinone oxidoreductase; The monomer polymer material is any one or more of 2-methylallylamine, N,N-dimethylacrylamide, 2-(diethylamino)ethyl methacrylate, 2-(dimethylamino)ethyl methacrylate, propyl methacrylate, 3-methylbut-3-en-1-amine, allylamine, allyltrimethylammonium chloride and diallyldimethylammonium chloride.
2. The composite enzyme nanogel according to claim 1, characterized in that: In the composite protease: 1) The mass ratio of glucose oxidase to catalase is 0.5:(0.1-15); or 2) The mass ratio of superoxide dismutase to catalase is 0.1:(0.5-30); or 3) The mass ratio of horseradish peroxidase to catalase is 0.2:(1-10); or 4) The mass ratio of lactate oxidase to catalase is 0.1:(0.2-12); or 5) The mass ratio of any one of glutathione peroxidase and lactate oxidase to catalase is (1-10): (0.5-15); or 6) The mass ratio of any one of glucose oxidase, superoxide dismutase, horseradish peroxidase, glutathione peroxidase, lactate oxidase, catalase and heme oxygenase is (2-30): (5-15): (3-20); or 7) The mass ratio of glucose oxidase, superoxide dismutase, horseradish peroxidase, glutathione peroxidase and lactate oxidase, catalase and quinone oxidoreductase is (1-15):(2-25):(1-30).
3. The composite enzyme nanogel according to claim 1, characterized in that: The binder is at least one of acrylamide, acrylic acid, 2-hydroxyethyl acrylate, N-isopropyl acrylamide, methacrylate glyceride, methacryloyl hydrazide and 3-allyloxy-1,2-propylene glycol.
4. The composite enzyme nanogel according to claim 1, characterized in that: The crosslinking agent is at least one of allyl methacrylate, N,N'-methylenebisacrylamide, poly(ethylene glycol) diacrylate, multi-arm poly(ethylene glycol) diacrylate, N,N'bis(acryloyl)cystamine, N,N'-(1,2-dihydroxyethylene)diacrylamide, N,N-diallylacetamide, N-methyldiallylamine, triallylamine, 1,3-bis(propyleneoxy)-2-propanol, N,N'-diallyltartaric acid diamide, 1,3-diallyl-2-thiourea and ethylene glycol dimethacrylate.
5. The composite enzyme nanogel according to claim 1, characterized in that: The particle size of the complex enzyme nanogel is 10 to 1000 nm.
6. The method for preparing the composite enzyme nanogel according to any one of claims 1 to 5, characterized in that: The steps include: The composite protease is weighed by weight and placed in a solvent, and a monomer polymer material is added, and the mixture is reacted for 2 to 12 hours under stirring at room temperature to obtain a mixture; the mixture is nitrogen blown for 1 to 3 hours, a cross-linking agent and a binder are added, and the mixture is stirred and reacted for 3 to 10 hours to obtain the composite enzyme nanogel.
7. The preparation method according to claim 6, characterized in that: The mass volume ratio of the composite protease to the solvent is 1:(5-20).
8. The preparation method according to claim 6, characterized in that: The preparation step also includes: filtering and sterilizing the prepared composite enzyme nanogel.
9. Use of the complex enzyme nanogel according to any one of claims 1 to 5 in the preparation of drugs for treating cancer, inflammatory diseases, diabetes or infections.
Citation Information
Cited By
A recombinant natural enzyme nanogel as well as a preparation method and application thereof
CN122624722A